Impact factors—a critique - Ramsden, Jeremy J. (Collegium Basilea & AMSI, 2009)
The so-called impact factor (IF) started as a rather esoteric scientometric tool, itself derived from the science citation index (SCI), which originated with Eugene Garfield in the 1950s. The IF of a journal for a particular year is defined as the quotient of the number of citations received in that year by papers published in that journal in the two preceding years and the number of “citable” papers published in those two years. Had the IF remained, as might have been reasonable to expect, a specialist statistic mainly of interest to information professionals as represented by librarians and others there would be no need to expend energy on criticizing it. Unfortunately its use—or rather misuse—has vastly expanded in recent years, which makes criticism very necessary.